Redefining retail experience in the next normal through sense of place and attributes evaluation in Regional shopping centers in Davao City - Soliva, Jayvee L.; Pernes, Nory Loyd N. (2023)
Shopping centers have been currently challenged by the impacts of the COVID-19 pandemic and online shopping platforms, resulting in changes in shopping preferences and behavior among different demographics, low foot traffic, and high retail vacancies. To adapt to these post-pandemic challenges, redefining the retail experience by enhancing its physical attributes and the Sense of Place of both shoppers and retailers is needed. The study sought to document and describe the physical attributes of selected regional shopping centers in Davao City; to correlate the physical attributes and the Sense of Place; to correlate the Sense of Place and shopping behavior of customers; and to establish architectural guidelines that will enhance the post-pandemic retail experience. Data were gathered through photo documentation and survey questionnaires on a 5-point Likert scale distributed to 220 respondents. Moreover, Sense of Place scores correlated with the attributes using Pearson?s correlation coefficient; and Shopping Behavior using Spearman's ? coefficient. Results showed that none of the attributes of regional shopping centers are in excellent condition. The existing attributes of the regional shopping centers had a weak correlation to place identity for the shoppers, which is crucial in building a sense of place. The main dimensions of the sense of place, specifically place satisfaction and place attachment, had a strong correlation with Ambiance, Atmosphere, Leisure Offers, Mall Management, and Parking, for both shoppers and retailers.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023